2004
DOI: 10.1002/gcc.20075
|View full text |Cite
|
Sign up to set email alerts
|

Alternative mechanisms of gene amplification in human cancers

Abstract: Gene amplification is a common phenomenon in cancer. Cytogenetic analyses have indicated that breakage-fusion-bridge (BFB) cycles drive intrachromosomal amplification of some oncogenes in a head-to-head manner in human cancers. However, the complex structures of an amplified sequence found in cancers are not always explained by the BFB model. At the 17q21 locus, which is not linked to common fragile sites, we discovered a recombination hot spot harboring amplicon repeats in tandem in a head-to-tail orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Any increase in parts of genome containing oncogenes, such as HER-2/neu, would play a key role in the onset and development of tumors (16,17). Overexpression of HER-2/neu gene has been reported in 92-95% of gastric cancer cases (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Any increase in parts of genome containing oncogenes, such as HER-2/neu, would play a key role in the onset and development of tumors (16,17). Overexpression of HER-2/neu gene has been reported in 92-95% of gastric cancer cases (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…1,3,4 According to the breakage-fusion-bridge model of amplification, the initiating event in HSR formation is double chromatid breakage at a fragile site or telomere erosion, 2,26,27 fused sister chromatids and breaking of the anaphase bridges. 28 Breakage-fusion-bridge cycles could then result in inverted amplified structures, 29 and the mutated sister chromatids are distributed to the daughter cells giving rise to intra-tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Chromosomal abnormalities associated with DNA amplification can be organized as extrachromosomal copies, called double minutes (dmins); in tandem arrays as head-to-tail or inverted repeats within a chromosome, often forming a cytologically visible, homogeneously staining region (HSR); or distributed at various locations in the genome (distributed insertions). 1,3,4 The most frequently amplified genes in cancers are MYCN, ERBB2 and EGFR. 4 The epidermal growth factor receptor (EGFR) is a cell membrane receptor with intrinsic protein tyrosine kinase activity, which has been the subject of rigorous investigation due to its involvement in several human cancers and its potential as a target of therapy.…”
mentioning
confidence: 99%
“…Fluorescent in situ hybridization (FISH) and other studies have shown that amplicons may be composed of DNA from multiple different parts of the genome (Guan et al 1994;Muleris et al 1995;Volik et al 2003Volik et al , 2006Lim et al 2005;Van Roy et al 2006). Where the amplified DNA is from the same genomic region, both inverted orientation of amplified repeat units (Hellman et al 2002;Herrick et al 2005) and noninverted (tandem) orientation (Amler et al 1992;Kuwahara et al 2004;Vogt et al 2004;Herrick et al 2005) have been reported. Each of these patterns may reflect different pathogenetic processes.…”
mentioning
confidence: 99%